Logical meaning in the discourse on refugee: A systemic functional analysis of Rohingya’s arrival rejection news in Indonesia - Yusuf, Muhammad; Syahputra, Fikry Prastya; Hamamah, Hamamah; Sahiruddin (Research Journal in Advanced Humanities, 2024)
The Rohinya’s arrival rejection in Aceh, Indonesia has been reported and become headlines in Indonesia and the world. Understanding how linguistic choices contribute to constructing the identity of the Rohingya within the news media is crucial for a nuanced analysis of the rejection narrative in Indonesia, this study explores the linguistic portrayal of the Rohingya in Indonesian media, particularly focusing on the rejection of Rohingya arrivals in Indonesia during 2023 through logical meaning based on systemic functional linguistic perspective. This research employed a qualitative content analysis design to investigate the linguistic portrayal of Rohingya rejection in Indonesian media during 2023, specifically focusing on 10 English news articles from The Jakarta Post. The selection of as the primary data source is based on its societal significance and popularity in Indonesia. The data were in the form of clause complexes. The findings show that the clauses are represented in paratactic and hypotactic in taxis system. In logico-semantic relation, expansion were realized in the form of extension, elaboration, and enhancement, while projection is realized in the form of locution and idea. Those variation shows of the objectivity and the fact presented in the news regarding Rohingya’s refugee condition.